Management control system and innovation : implication for Malaysian manufacturing innovation performance - Salma Khalidah Sa’adon; Amizawati Mohd Amir; Rozita Amiruddin (Penerbit Universiti Kebangsaan Malaysia, 2019)
The study extends prior management control system knowledge by observing the significance of the information generated in facilitating innovation efforts which, in turn, improves the innovation performance of firms. The paper explores the role of company mission and vision statement, job scope description, and performance measurement system as sources of management control information to support firms’ innovation activity and to manage their performance in facing present market demands. Survey was administered to the Product Development Managers randomly selected from the Federation of Malaysian Manufacturers Directory. Based on a total of 102 usable responses, evidence showed that firm’s value positively relates to firm’s innovation activities. The study discovers that diagnostic information is positively significant with incremental innovation, whereas interactive information is significantly associated with radical innovation. Evidently, both types of innovation enhance a firm’s innovation performance. Rather than assessing the immediate return of innovation efforts on firms’ financial performance, the study provides support showing both types of innovation do enhance firms’ innovation performance.